Effect of mycorrhizes in fertilization form management complementary cultivation in the corn (Zea mays) - Macías Hernández, David; Vargas Guillén, Pablo Israel; Villota Chóez, Mercedes del Rocío; Castro Cabeza, Dionis (SATHIRI, 2023)
This article presents the findings of a research project carried out in the Yaguachi canton, Guayas province, on the reduction of the use of fertilizers and the use of the benefits of microorganisms, as well as their relationship with the absorption of water and essential nutrients in plants and increasing its production. The general objective is to measure the effect of the different levels of mycorrhizae for the improvement of the management of the maize crop (Zea mays), of the hybrid variety Trueno NB7443, in which a completely randomized block design with 4 treatments was used. and 6 repetitions resulting in 24 experimental units where different doses are applied. The Tukey test was used at 5% probability of error to determine different significances in the agronomic behavior of the variety. Four treatments were used: T1 with the 50g dose of Quinta Aura mycorrhizae and 50g of NITROK in measurements of 15, 30, 45 days, which when harvested stands out from the rest in variables such as yield. Among the results obtained, it was possible to appreciate ears that were much more vigorous and with a higher proportion of grains and a better cost-benefit ratio of 1.23, and with a yield of 3,120 kg/ha. Additionally, within the following treatments; T2 (100gr of Mycorrhizae) with a yield of 2,625ha, T3 (NITROK), evidenced significance in terms of yield of 2,533kg/ha and T4 (control) thus yielding a yield of 2,901kg/ha.
Keywords: Corn; mycorrhizae; NITROK; Thunder NB 7443